Implementation of Islamic Religious Education Learning and Character in the New Normal Era - Zainal Abidin; Dina Destari; Syafruddin Syafruddin; Syamsul Arifin; Mila Agustiani (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
This article aims to describe the planning, implementation, and evaluation of IRE (Islamic Religious Education) and Character learning at SMK Thoriqul Ulum Pacet. This article uses qualitative research with a case study approach. For data collection, researchers used observation, interviews, and documentation techniques. Data analysis techniques were carried out by data reduction, data presentation, and conclusion drawing. This study obtained the following results: 1) General learning planning, a) determination of health protocols, b) preparation of lesson plans, c) face to face assessment during the new standard period d) evaluation. 2) Implementing Islamic Education and Character Learning in the New Normal Era at Thoriqul Ulum Pacet Vocational School using face to face but reducing learning hours. 3) Evaluation of Islamic Education and Character Learning in the New Normal Era at Thoriqul Ulum Pacet Vocational School with the teacher giving exams, oral tests, assignments, and homework.